Investigation of remelting effects on controlling microstructure morphology in powder bed fusion - Wong, Wendell Shun Yin (Nanyang Technological University, 2022)
This research investigates the effects of remelting on 316L stainless steel fabricated using laser powder bed fusion (L-PBF), specifically selective laser melting (SLM). Surface roughness, hardness, porosity, UTS and max elongation were assessed in this study, in addition microstructure morphology will be compared to simulation. Remelting leads to improved hardness in low energy density (ED) specimens from 216.41 ± 10.12 HV for single scan to 234.12 ± 7.43 HV for remelted specimens. Remelting has a positive effect on density due to decreased defect occurrence across the layers for regular ED specimens and better fusion. Density is improved from 7.876 ± 0.06 g/m3 to 7.910 ± 0.03 g/m3. The porosity of the specimens decreased from 0.15 % to 0.12 % and their surface roughness also decreased from 22.65 ± 2.04 µm to 14.5 ± 2.08 µm. In addition, variability was substantially reduced. Analysis of Variance (ANOVA) has highlighted that main factor such as laser power, scanning speed and hatch spacing and their interactions which affect ED improve the specimens’ physical properties. Ultimate tensile strength (UTS) has improvements between 16.58 % to 21.45 % from 528.5 ± 58.5 MPa to 641.9 ± 16.4 MPa while maximum elongation, has improvements between 8.78 % to 19.55 % from 38.70 ± 1.56 % to 46.27 ± 2.74 %. Optical micrography have shown remelting is able to produce consistent repeating melt pools forming zig zag pattern. Simulation is able to approximate melt pool width and depth within a difference of 3.620 ± 0.637 % and 13.825 ± 1.180 %. Rough approximation of expected microstructure morphology can be approximated by corroborating with simulated thermal gradient. ED below 30 J/mm3 shows grains that are constraint within the melt pool and shows a shallower thermal gradient via simulation. Above 30 J/mm 3 shows grains growing beyond the melt pool and a steeper thermal gradient.